Pengaruh Tingkat Suku Bunga, Nilai Tukar, dan Foreign Direct Investment (FDI) Terhadap Ekspor Non-Migas Di ASEAN - Shalsa Calista Azhaly; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Abstract This study aims to examine how interest rates, exchange rates, and foreign direct investment (FDI) affect the performance of non-oil and gas exports in the ASEAN region during the period 2009-2023. The research approach uses a quantitative method based on panel data regression, utilizing secondary data from Bruegel, Trading Economics, and the ASEAN Statistical Yearbook. The main variables analyzed include interest rates, exchange rates, and foreign direct investment (FDI) on non-oil and gas exports in the 10 ASEAN member countries. The analysis results indicate that interest rates have a negative and significant impact, while exchange rates have a positive but insignificant impact, and FDI has a significant positive impact. These findings emphasize the need to maintain exchange rate stability, increase productive foreign investment, and implement monetary policies that support the competitiveness of non-oil and gas exports. Additionally, strengthening domestic production capacity is a crucial strategy for ASEAN to sustain non-oil and gas export growth amid global trade challenges. Keywords: interest rate, exchange rate, foreign direct investment, non-oil and gas export